Optimization of the drilling parameters for the cutting forces in B4C-reinforced Al-7XXX-series alloys based on the Taguchi method - Taşkesen, Ahmet (Materiali in tehnologije, 2013)
In this study, drilling tests of aluminum-based composites produced with the powder-metallurgy (PM) technique and reinforced with boron-carbide (B4C) particles were carried out with three different types of drills under dry cutting conditions. In order to determine the mechanical properties of the produced composites, hardness and tensile tests were performed. Moreover, the effects of the machining parameters such as cutting speed, feed rate, particle fraction and cutting-tool material, and of their interactions on the thrust force and cutting torque were determined with the Taguchi experimental design. Drilling parameters were optimized in terms of cutting forces (thrust force and torque). Furthermore, an analysis of variance (ANOVA) was conducted to obtain the degree of the effect of the parameters. The most influential control factors for the cutting forces were found to be the particle fraction and feed rate. According to the experimental results, the thrust force and cutting torque increased significantly as the feed rate or the particle content increased. On the other hand, the influence of the drill-bit material and the interactions of the factors for the cutting forces were quite low.
Keywords: composites; kompoziti; powder metallurgy; prašna metalurgija; drilling; vrtanje; sila rezanja; cutting force; Navar; navor; torque; Taguchi method; Taguchijeva metoda